Defectologia soviética e a deficiência intelectual : contribuições para a formação e atuação do psicólogo para o atendimento educacional especializado - Silva, Aline Cardoso da (2011)
This dissertation is the result of literature search, carried out from 2009-2011, linked to the Graduate Program in Psychology, State University of Maringá (UEM-PPI).The research theme was the contributions of Soviet studies of disabilities focused on intellectual disability for the training of psychologists and their work with special education or specialized educational services. The objectives were to identify and propositions of Vygotsky and other contemporary authors to their Defectology Russian, with a focus on intellectual disabilities; further elaborations on the theoretical and methodological approaches of historical-cultural psychology as to how the person with intellectual disabilities to learn and develops, to discuss contributions to the formation and work of a psychologist with the specialized educational services. Justified their achievement compared to their line of research linking psychosocial constitution of subjectivity and knowledge and the research project Historical-Cultural Psychology and Defectology: a study of contributions / theoretical and methodological implications for the Soviet appropriation of verbal language by students with disabilities and the constitution of their subjectivities. The research followed the Historic-Cultural Psychology and the Soviet Defectology. He was elected as the primary sources of cognition in specific works and secondary sources such as authors and employees that reference the Russian author and its theory. It stands out, with the investigation, the Vygotskia theory offers directions to our classroom and the psychologist, as well as new conceptions of man he is poor or not. Based on the foregoing, we conclude that the practice of a psychologist at the way they are being performed helps to maintain an ideology of social force, and through the appropriation of Vygotskia theory it is possible to break this form of action and propose a psychology engaged transformations social.